Spatial Development of the Novosibirsk Region - Evgeniya Anatolievna Kolomak (Prostranstvennaâ Èkonomika)
The paper presents a study of differences in the economic development of municipalities in the Novosibirsk region. Based on official statistics, maps of the distribution across the territory are built for population, employment, revenue, profitability of sales, and the share of unprofitable enterprises. The conclusion is that there is a high degree of concentration of business activity around the regional capital. At the same time, not all municipalities of the Novosibirsk agglomeration are leaders in terms of growth rates and business efficiency, which raises the question of exhausting the resource of the positive effects of the agglomeration economy. Descriptive methods are complemented by an econometric analysis of the role of spatial factors in the economic development of territories. Regression estimates revealed the heterogeneity of the influence of external markets, the positive effects of inter-district relations dominate within the Novosibirsk agglomeration, but the negative effects of inter-municipal competition are more pronounced outside it. Further concentration of economic potential in the Novosibirsk agglomeration without a longer transmission of growth impulses to other urban and rural settlements will lead to a restraint on the development of the entire territory of the region. Regional policy should include institutions and mechanisms for the transition from mostly competitive relations between municipalities to the predominance of cooperative interests. It is also necessary to create conditions for the creation of new centers of economic growth in the region, their role can be performed by municipalities with a relatively high population, with a developed road network and with a predominantly industrial specialization of business activity